Agrobiznes a logistyka - Wincewicz, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article discusses the place of agribusiness in the logistics, system of economics. The author tries to show the connections between agriculture and environments and others levels of logistic systems. Agriculture productions need very special knowledge about nature productions, and business systems. This is why the logistic can be very useful in finding the solutions for agribusiness problems and dilemmas. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 359-366